Optimal redistributive taxation in a multi-externality model - Paul Eckerstorfer (Johannes Kepler University of Linz, Department of Economics, 2011)
This paper extends the previous literature on optimal redistributive taxation in the presence of externalities to a multi-externality setting. While taxes on income and on 'clean' commodities are still unaffected by the externalities, which confirms previous results, I find that the existence of more than one externality-generating commodity has important implications for the optimal Pigouvian tax rates. In general the Pigouvian parts of taxation depend also on the externalities induced by the consumption of the other commodities, implying that the interdependence of the externality-generating commodities is relevant for tax policy.
Keywords: D82; H21; H23; H24; 330; Optimal Taxation; Externalities; Einkommensteuer; Verbrauchsteuer; Optimale Besteuerung; Internalisierung externer Effekte; Theorie